Postlingual Impairment and its Impact on the Development of thepupils’ Linguistic Competence - Belkhairi, Adel (Journal of Human Sciences, 2022)
In the light of the use of applied linguistics in various fields to solve different linguistic issues, this research attempts to highlight the impact of Postlingual impairment on the linguistic competence and performance of the elementary school pupil in order to overcome many learning difficulties for those who have such disability. In fact, those pupils with this disability seem like normal pupils since their disorder is at an advanced phase of linguistic attainment. Therefore, instructors, at this stage, must be up-dated and informed about this disability and the skills needed to identify its characteristics and how to deal with a disabled pupil. Moreover, its negligence leads to the lack of linguistic attainment which in its turn may cause early school dropout.